Democratic Science Teaching: Building the Expertise to Empower Low-Income Minority Youth in Science
VI, 127 p.
Keywords: Democratic science pedagogy has the potential to shape learning outcomes and science engagement by taking on directly issues of pedagogy, learning, and social justice. In this text we provide a framework for democratic science teaching in order to interrogate the purposes and goals of science education in classrooms globally, as well as to call attention to ways of being in the classroom that position teachers and students as important and powerful participants in their own learning and as change-agents of a larger global society. We develop three core conceptual tools for democratic science teaching, that together frame ways of thinking and being in classrooms that work towards a more just world: Voice, Authority, and Critical Science Literacy. Each conceptual tool is developed in the introductory chapters then taken up in different pedagogical and analytic ways in the chapters that span the text. The chapters present researcher, teacher, and student centered lenses for investigating democratic science education and reflect elementary through high school education, both in school and out of school, in the US and globally.